The roles of strategic alliances, innovation capability, and cost reduction in enhancing customer loyalty and a firm’s competitive advantage in B2B alliances - Musa, Soebowo (Emerging Markets : Business and Management Studies Journal, 2024)
Disruptive business environments such as the COVID-19 pandemic and the recent high volatility in commodity prices have changed the way businesses are conducted. The heavy equipment industry is one of many industries affected by such an environment, especially those who are related to the mining industry where the volatility of the commodity prices has a significant impact on their business performance. Alliances are commonly formed by heavy equipment distributors and their customers to create a mutual benefit to sustain their performance. Strategic alliances have attracted substantial attention from industry as well as academia as a way to stay competitive. They mostly focus on partner-to-partner alliances in serving their customers. Consumer behaviour has changed due to changes in the environment that make firms' strategic focus more on human-centric business approaches. This study looks at the roles of partner-to-customer alliances, innovation capability, and cost reduction toward customer loyalty and competitive advantage. Data was collected from 335 respondents from the firms that have entered into alliances. This study finds strategic alliances have the highest association with cost reduction, followed by their association with innovation capability. They enhance customer loyalty through innovation capability. Cost reduction is not a lever to develop customer loyalty in the partner-to-customer relationship. The study also confirms the paramount importance of operational efficiencies in gaining a competitive advantage, with strategic alliances playing a significant role in this aspect. Keywords: strategic alliances, innovation capability, cost reduction, customer loyalty, competitive advantage.